Analisis Sebelum dan Sesudah terhadap Kecelakaan Lalu Lintas dalam Kaitannya dengan Pelebaran Jalan di Kota Batam - Tandi lawa, Aldo; Rifai, Andri Irfan; Prasetijo, Joewono (Universitas Batanghari Jambi, 2026)
The growth of urban activity in Batam City as a major industrial and commercial area has significantly increased traffic volume and caused traffic congestion and road safety issues. As a result, the local government has widened a number of main roads in an effort to increase infrastructure capacity, but the impact on traffic safety still needs to be comprehensively evaluated. This study aims to analyze the effect of road widening on traffic safety levels in Batam City. The research method used is a pre-post analysis approach, combining secondary data on traffic accidents for the period 2021-2025 from the Barelang Police Traffic Unit and primary data in the form of a perception survey of 350 road users on sections that have undergone widening. The results show that road widening contributes to improved traffic flow and shapes the public's perception that the number of accidents is declining. However, official accident data still shows an increase in the number of incidents, even though the fatality rate has relatively decreased and there is a tendency for vehicle speeds to increase. Therefore, road widening cannot be used as a sole solution to improve traffic safety and needs to be integrated with speed control, improved road safety facilities, and sustainable traffic management